Mental health research in the Arab region: challenges and call for action. (November 2019) - Maalouf, Fadi T; Alamiri, Bibi; Atweh, Samir; Becker, Anne E; Cheour, Majda; Darwish, Hala; Ghandour, Lilian A; Ghuloum, Suhaila; Hamze, Mouin; Karam, Elie; Khoury, Brigitte; Khoury, Samia J; et al.
Summary: Although mental disorders are a leading cause of disability in the Arab region, which includes 5·54% of the global population, Arab countries produce only 1·0% of the global output of peer-reviewed publications in mental health research. Various stakeholders, including Arab mental health researchers, institutional and funding agency officials, and international research collaborators, convened to identify challenges faced by Arab mental health researchers and propose an evidence-informed call for action. Challenges identified include prevalent stigma and low awareness, conflict and war, scarce institutional and funding resources, inadequate publishing opportunities, insufficient training in mental health research, and shortage of reliable and valid assessment tools. The proposed action plan includes ways of addressing stigma and spreading awareness, increasing collaborative efforts, building research infrastructure, strengthening the mental health workforce, and translating research findings into a call to action on societal and governmental levels. The proposed action plan could provide a roadmap for Arab mental health researchers and research institutions, which might ultimately increase research productivity in the Arab region and close the gap between Arab countries and the rest of the world.